HISTORY OF EDUCATION IN THE COUNTRIES OF THE WORLD - Yoziyeva Umida Lutfullayevna (American Journals, 2025)
This article discusses the emergence of educational systems in countries around the world, the first pedagogical views. Special attention is also paid to the specific features of European education, new reforms, opportunities, achievements, and a comparative analysis of the European education system.
Keywords: Europe, countries of the world, developed countries, pedagogical views, education system, education sector, curriculum, pre-school education, primary education, general secondary education, higher education, characteristics, educational institution.